STRATEGIC ASPECTS OF BREAK-EVEN DEVELOPMENT OF HUNTING FARMS IN THE POST-WAR PERIOD - Yavorska , Т.; Sobolevska , О. (Bulletin of Lviv National Environmental University. Series "AIC Economics", 2024)
The text discusses an approach to managing the incomes and expenses of hunting farms while minimizing the negative impact of human activities. It is highlighted that the strategic priorities of the break-even development of hunting farms in the post-war period are based on the principles of cost self-sufficiency parameters in the context of their economic relations with forest and agricultural entities in a certain area of their location and an integrated approach to the restoration of stable economic growth and resource opportunities. It was determined that the balancing of the economic cycle of hunting farms and their break-even development is possible by placing funds in ecological projects based on the combination of methods of self-recovery of costs with methods of subsidizing and stimulating environmental protection measures. A comprehensive methodology for assessing the level of environmental sustainability of the natural capital of hunting farms is proposed, which allows determining the economic benefit with consideration of the ecological component. A toolkit for assessing the level of environmental sustainability of the natural capital of hunting farms in Zaporizhzhia region has been developed. It has been proven that under the condition of deoccupation of the territories, the implementation of strategic programs for the loss-free development of hunting farms in Zaporizhzhia region based on environmental policy will allow to increase the costs for the restoration of natural capital. It is substantiated that the resource capabilities of hunting farms of Melitopol district of Zaporizhzhia region in 2024–2026 will allow to increase the level of their break-even development, provided that budget investments are made in the greening of natural capital and will be restored with their rational use.